Contribution of grains and grain boundaries to dielectric relaxations and conduction of Aurivillius Bi4Ti2Fe0.5Nb0.5O12 ceramics. Issue 10 (December 2015) - Rehman, Fida; Li, Jing-Bo; Cao, Mao-Sheng; Zhao, Yong-Jie; Rizwan, Muhammad; Jin, Hai-Bo
Abstract: The dielectric response and electrical properties of Bi4 Ti2 Fe0.5 Nb0.5 O12 (BTFN) ceramics have been investigated by frequency and temperature dependent dielectric/impedance spectroscopy. The detailed frequency spectrum analysis demonstrates the existence of two dielectric relaxations in the ceramics. The high-frequency relaxation is evidenced to originate from the grains and the low-frequency relaxation is ascribed to the contribution of grain boundaries. The resistance of grain boundaries is much larger than that of grains, whereas the values of capacitance of grain boundaries and grains are in the same level. Above 340 °C, the conduction and relaxations of the material are attributed to the motion of ionized oxygen vacancies. As temperature above 540 °C is close to the ferroelectric transition temperature, the smart dielectric response to the external applied ac field was apparently reflected by the conductance of grain boundaries, the capacitance of grains and the consequent relaxations.